Home » Aptitude » Algebra » Question
  1. If 3a2 = b2 ≠ 0, then the value of
    (a + b)3 - (a - b)3
    is
    (a + b)2 - (a - b)2

    1. 3b
      2

    2. b
    3. b
      2

    4. 2b
      3
Correct Option: A

Expression =
(a + b)3 - (a - b)3
(a + b)2 + (a - b)2

Expression =
(a3 + b3 + 3a2b + 3ab2) - (a3 - b3 - 3a2b + 3ab2)
(a2 + b2 + 2ab) + (a2 + b2 - 2ab)

Expression =
(a3 + b3 + 3a2b + 3ab2 - a3 + b3 + 3a2b - 3ab2)
(a2 + b2 + a2 + b2)

Expression =
(6a2b + 2b3)
2(a2 + b2)

Expression =
2b(3a2 + b2)
2(a2 + b2)

Expression =
b(b2 + b2)
b2
+ b2
3

Expression =
b × 2b2
4b2
3

Expression =
b(3 × 2)
=
3b
42



Your comments will be displayed only after manual approval.